The funniest joke book ever for kids - Katz, Alan (New York, NY : Scholastic Inc., 2024)
Careful, the jokes in this book are so funny you might just laugh your socks off! From knock knocks to puns a plenty, The Funniest Joke Book Ever For Kids is positively overflowing with fun. It even has activities and fun ideas for the prankster in all of us. Can you read the whole thing without laughing? Bet you can't! And it's all brought to you by author and funny man, Alan Katz.
3-6
Keywords: Wit and humor, Juvenile; Wit and humor; Humor; Jokes; Puns and punning; Knock-knock jokes -- Juvenile literature; Practical jokes